The use of underwater active and passive acoustics to locate and study fishes - Anthony D Hawkins (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
This paper describes how fish can be located using sound, especially in the sea, but also in rivers and lakes. It describes the use of sound detections, including both passive and active acoustics, and it reviews each of these technologies and shows how they can be used to understand the distribution of sound-producing species and to examine information on the spawning habitats of fishes, and their spawning behavior, and also their movement patterns. Sounds generated by humans can have detrimental effects upon fishes, and some stocks of fishes are exploited close to their safe biological limits, requiring restrictions upon those human activities that may harm them. There is a need to regulate those human activities that have adverse effects on fish.